Who Doesn't Want to be a Leader? Leaders Are Such Wonderful People Comment on "Leadership and Leadership Development in Healthcare Settings - A Simplistic Solution to Complex Problems?" - Mark Learmonth (Kerman University of Medical Sciences, 2015)
Leadership, as McDonald (1)argues, is a phenomenon which many people involved in healthcare around the globe put great emphasis on today; some even see the improvement of leadership as a panacea for all the ills of their healthcare system. This brief commentary on her work seeks to supplement the points she makes by emphasising the personalattractions leadership enjoys, at least in the eyes of many of those who exercise power in healthcare. It also endeavours to highlight some of the ironies and absurdities which arise as a result of the conflicts about what terms we should use to describe the "leaders" (or, alternatively perhaps, those who seek to enjoy supremacy) within healthcare.